IMPROVED UNDERSTANDING OF CONCEPTS THROUGH CTL ASSOCIATION THINK-PAIR-SHARE TECHNIQUE - Sesrita, Afridha (Universitas Djuanda, 2016)
Understanding the concept of students material, concepts, reasoning, formulas and problems related to physics for learning and participation, active and motivated students were increasingly low, predictable when explaining a concept, the teacher does not associate the material with studentâs real world. Need to create a joyous atmosphere and conducive learning so that students become interested in following the lesson, motivated, active and participating. Therefore, if it were necessary research to see the effect of CTL associated Think-pair-share Technique in improving the understanding of physics concepts. The research hypothesis is that there is a meaningful impact CTL associated Think-pair-share Technique in improving the understanding of physics concepts. This type of research is an experimental research design randomized control group only design. The study population was the whole class. Sampling through random sampling techniques and obtained experimental class (class VIII-1) and the control class (VIII-3). Data analysis techniques in the view of understanding the concept of student t test. The results were obtained understanding of the concepts of physics experiment grade students was higher than the control class. After using the t test obtained t = 6:24 larger than table = 1.99802 on the real level of 0.05 and df = 66. This means that the research hypothesis (H_i) which reads